Neurologic injuries in skiers and snowboarders - Levy, A. S.; Smith, R. H. (Seminars in Neurology, 2000)
Neurologic injures are the leading cause of death and disability in skiing and snowboarding accidents, despite accounting for only a small fraction of injuries overall. Head injuries make up 3 to 15% of all skiing and snowboarding related injuries, spinal injuries account for 1 to 13%, and peripheral nerve injuries constitute less than 1% of reported injuries. Improvements in equipment and technology, especially advances in binding technology, have resulted in decreased injury rates on the slopes overall, but neurologic injury rates have not decreased, and in fact appear to be increasing as a percentage of overall injuries and in absolute numbers. With advances in technology and slope maintenance, skiers and boarders progress to higher skill levels and faster speeds more rapidly than ever before. Great efforts have been focused on reducing extremity injuries in skiers and snowboarders, but until recently very little attention has been given to neurologic injury prevention on the slopes. Hopefully with increased awareness and the growing popularity of ski/snowboard helmets, we will begin to see head injury rates (and maybe even spine injury rates) decrease among skiers and snowboarders.